Peran Sekolah Ramah Anak Dalam Penguatan Kearifan Lokal Bagi Siswa Miskin Ekstrem Sekolah Dasar di Balikpapan - Casmudi, Casmudi; Indriawati, Prita; Waskitoningtyas, Rahayu Sri (Jurnal Penelitian Agama Hindu, 2025)
Child-Friendly Schools in Balikpapan currently have not yet built local wisdom for their students, especially in the context of education and daily life. This local wisdom can be utilized as a culture-based approach to support them socially, emotionally, and practically. The objectives of this study (1) explain the form of involvement of parents and school committees in the local wisdom of Child-Friendly Schools (SRA); and (2) explain the experiences of extremely poor students (SME) regarding the comfort of learning motivation. The subjects of the study were selected from extremely poor students in Elementary Schools (SD) in Balikpapan, together with teachers, principals, and parent representatives. This type of research refers to qualitative research. The sample was determined purposively, namely SDN 001 Balikpapan Timur, SDN 002 Balikpapan Selatan, SDN 001 Balikpapan Kota, SDN 004 Balikpapan Barat, SDN 009 Balikpapan Utara, and SD Kumala Bhayangkari. Data collection involved in-depth interviews with students, teachers, and principals, observations of classroom learning habits, and analysis of related documents. Data were analyzed inductively, with a theoretical basis of phenomenology to understand subjective experiences, ethnography for cultural context, and discourse analysis for language interpretation. The main result is that child-friendly school education can build local wisdom in extremely poor students. In conclusion (1) child-friendly school learning for Extreme Poor Students requires support from parents, committees and services to help their stability, emotions and mentality; and (2) improving learning outcomes, individual approaches, social assistance and strengthening teacher motivation are effective strategies to improve student experiences related to motivation for learning outcomes.